2014
DOI: 10.3747/co.21.2056
|View full text |Cite
|
Sign up to set email alerts
|

Screening Histories and Contact with Physicians as Determinants of Cervical Cancer Risk in Montreal, Quebec

Abstract: ConclusionsOur findings provide evidence of the need for an organized population-based screening program. They also underscore the need for provider education to prevent missed opportunities for cca screening when at-risk women seek medical attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The survey was designed based on other cervical cancer studies. [13][14][15][16][17] The survey instrument was 13 pages with 27 questions estimated to take 15 minutes to complete. It consisted of five sections, including (1) cervical cancer history (including whether the survivor was diagnosed as the result of a routine examination or was seeking medical care related to symptoms), use of cervical cancer screenings and follow-up for abnormal tests in the 5 years before diagnosis, and barriers and facilitators to screening and any necessary follow-up; (2) health insurance; (3) other medical conditions; (4) respondent demographic characteristics; and (5) interest in cervical selfsampling technology, HPV vaccination of children, and awareness of HPV before diagnosis.…”
Section: Surveymentioning
confidence: 99%
“…The survey was designed based on other cervical cancer studies. [13][14][15][16][17] The survey instrument was 13 pages with 27 questions estimated to take 15 minutes to complete. It consisted of five sections, including (1) cervical cancer history (including whether the survivor was diagnosed as the result of a routine examination or was seeking medical care related to symptoms), use of cervical cancer screenings and follow-up for abnormal tests in the 5 years before diagnosis, and barriers and facilitators to screening and any necessary follow-up; (2) health insurance; (3) other medical conditions; (4) respondent demographic characteristics; and (5) interest in cervical selfsampling technology, HPV vaccination of children, and awareness of HPV before diagnosis.…”
Section: Surveymentioning
confidence: 99%
“…Previous studies have revealed a higher risk of cervical cancer among women who seldom participate in screening or those not screened, compared with regularly screened women [ 21 , 22 ]. Notably, studies have reported a higher risk of the disease among some immigrant groups compared with non-immigrants in several countries offering a universal screening programme [ 4 , 11 , 12 , 16 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies highlight that, there still high proportion of CC patients that had irregular or no screening done despite the effectiveness and availability of this CC screening in the most developed countries (Spence AR et al, 2014). There also few studies reported that immigrants has low CC screening participation if we compare with non-immigrant women in different regions, which indicating that the screening participation among immigrants varies within and across various ethnic groups .…”
Section: Introductionmentioning
confidence: 85%